Nasrin Gone Global: A Critique of Taslima Nasrin’s Criticism of Islam and Her Feminist Strategy - Hasan, Md. Mahmudul (SAGE Publications, 2016)
Taslima Nasrin’s writings, which are extremely critical of Islam, have sparked controversy over the contents of her feminist work and strategy. Although many dismiss these writings as an anti-Islamic provocation, her ideas are well-received in the West, where she is celebrated as a feminist rebel who defies the supposedly suffocating Bangladeshi Islamic patriarchy. Unlike earlier Islamic feminists, especially Rokeya Sakhawat Hossain, who re-examined Islamic teachings in the light of locally prevalent gender discrimination, Nasrin directs her attacks against religion itself, putting almost the entire blame of gender injustice on it. In light of Rokeya’s work and strategy, and current struggles in Bangladesh to fine-tune the nation’s vision, the present article critically analyses Nasrin’s overly negative views of Islam and assesses the validity and efficacy of her feminist approach in Bangladesh society.